(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
The first operation of adsorption on leaf surfaces in pulverization is drop sticking. In the water wettability of the surfaces, the sticking of the drops has a great importance. Drop contact angle, contact height, and contact diameter values in the third and tenth seconds were measured with Drop Shape Analysis 10 device to determine adsorption, spreading, and sticking levels by applying mixtures of ten surface active substances including different contents with pure water to different leaf surfaces. The adsorption and sticking rates of the drops they formed on different leaf surfaces were determined for the time they are obtained from the data obtained in both time periods. Furthermore, the spreading rates of the mixtures prepared by taking into account the change rates during the last seven seconds between these two periods were determined as the sticking rate. Coating shares related to covering rates of different surface active substances with different surface properties on the surface of leaves were evaluated as possible work success according to the adsorption, spreading and sticking levels anticipated in spraying. According to their results on the application surfaces, surface active substances and leaves were evaluated statistically by the SPSS 15 program in terms of their similar properties. It has been found that surface active substance mixtures with sodium carboxymethylcellulose and carboxymethylcellulose contents had the largest drop contact angles and contact heights with the smallest drop contact diameters on the leaf surfaces, and a negative impact on the adsorption performance as they spread very little over seven seconds. It has been determined that drops with surface active substance including trisiloxane + allyloxypolyethyleneglycol and alcoholethoxylate, alkylphenolethoxylate have formed the smallest contact angles, minimum drop heights and largest contact diameters on the surface of the leaves, as well as increased adsorption and sticking by spreading rapidly for seven seconds.